Warming affects water use, yield and crop quality of a potato–broad bean–winter wheat rotation system in semi-arid regions of China. (1st September 2020) - Guoju, Xiao; Zhanqiang, Guo; Qiang, Zhang; Yanbin, Hu; Jing, Wang; Jin, Cao; Zhengji, Qiu
Abstract: Global warming will directly influence agricultural production and present new challenges for food security in semiarid regions of China. A warming experiment was conducted in Guyuan, China using infrared ray radiators to study the impact of warming on crop growth, yield and quality of a potato–broad bean–winter wheat crop rotation system. Warming significantly affected the crop photosynthesis rates of the potato–broad bean–winter wheat rotation system. In the podding stage of broad bean and the heading, blooming and booting stages of winter wheat, the photosynthesis rate was significantly decreased when the temperature increased by 0.5–2.0°C. The growing period of the potato–broad bean–winter wheat rotation system was shortened by 20–40 days per 3-year-period, and the fallow period was prolonged by 4–13 days per 3-year-period. The water use efficiency of the potato–broad bean–winter wheat rotation decreased by 8.6% when the temperature increased by 1.02.0°C. The yield of the potato–broad bean–winter wheat rotation increased by 6.1–7.7% when the temperature increased by 0.5–1.0°C. However, yield decreased 12.9–13.4% when temperature increased by 1.0–2.0°C. Potato protein significantly decreased by 9.3–17.6% and the winter wheat fat significantly decreased by 6.7% when the temperature increased by 0.5–2.0°C. The results indicate that global warming could seriously affect the crop growth, yield and water use of the potato–broad bean–winter wheat rotation in semiarid regions of China.